Navigating the path to effective End-of-Life Vehicle (ELV) management in Malaysia: a qualitative inquiry - Rosniza Aznie Che Rose; Charli Sitinjak; Rozmi Ismail; Zurinah Tahir; Zambri Harun; Muhamad Razuhanafi Mat Yazid (Penerbit Universiti Kebangsaan Malaysia, 2024)
The adoption of ELV (End-of-Life Vehicle) management policies holds excellent promise in Malaysia as a strategic response to the issue of abandoned vehicles. This qualitative study delves into the challenges and opportunities encountered in implementing sustainable ELV management in the country. Through semi-structured interviews and focused group discussions involving key stakeholders, such as experts, policymakers, industry representatives, and community members, this research identifies critical barriers obstructing the establishment of an efficient ELV management system. The findings underscore significant challenges stemming from the lack of a comprehensive legislative framework dedicated to ELV management and limited infrastructure for proper ELV collection and recycling, which hinder responsible waste management practices. Financial constraints and technological limitations further impede progress toward sustainable ELV management. Concurrently, improper ELV disposal practices and the escalating waste generation from the automotive industry present profound threats to Malaysia's environmental sustainability. Nonetheless, the study also highlights opportunities for improvement, including leveraging collaboration and knowledge exchange with developed nations and capitalizing on the rising market demand for recycled materials to drive resource recovery and circular economy practices. To overcome the identified challenges and capitalize on the opportunities, stakeholders must collaborate to establish an effective ELV management system, enhance public awareness, and enforce regulations. The study concludes by emphasizing the significance of strategic planning and investment in overcoming barriers and promoting sustainable ELV management practices in Malaysia, thereby contributing to a more environmentally conscious and sustainable automotive industry.